Inflammatory biomarker concentrations in dogs with gastric dilatation volvulus with and without 24-h intravenous lidocaine - Brunner, Anna; Lehmann, Anna; Hettlich, Bianca; Peters, Laureen M.; Doras, Camille Julie; Adamik, Katja-Nicole (Frontiers in Veterinary Science, 2024)
Background Canine gastric dilatation volvulus (GDV) is characterized by tissue ischemia, reperfusion, and systemic inflammation. Evidence exists that lidocaine exerts anti-inflammatory properties and potentially improves outcome. Design and setting Prospective, randomized observational cohort study in client-owned dogs with GDV. Objective The primary objective of the study was the determination of pro- and anti-inflammatory biomarker concentrations in dogs with GDV with and without intravenous (IV) lidocaine therapy. The second objective was the evaluation of side effects of lidocaine. Methods Of 35 dogs included in the study, 20 dogs were assigned to receive lidocaine (LIDO) (2 mg/kg initially, followed by a continuous infusion at a rate of 50 μg/kg/min over 24 h) and 15 dogs not to receive lidocaine (NO-LIDO). Plasma concentrations of cytokines interleukin (IL)-6, IL-7, IL-8, IL-10, IL-15, IL-18, interferon gamma, keratinocyte chemotactic-like, monocyte chemotactic protein, and C-reactive protein (CRP) were measured at admission (prior any therapeutic intervention, T0), immediately after surgery (T1), at 24 h (T24), and at 48 h (T48) post-surgery. Results No significant differences in concentrations of any cytokines were found between the LIDO- and the NO-LIDO group. Significant lower CRP concentrations (median [range]) were found in dogs with lidocaine compared to dogs without at T24 (97.5 pg/mL [46.3–161.7] vs. 127.9 pg/mL [26.9–182.0]; p = 0.046) and T48 (73.7 pg/mL [18.4–169.4] vs. 116.3 pg/mL [71.4–176.8]; p = 0.002). Dogs receiving lidocaine exhibited significantly impaired mentation, a prolonged period of anorexia, and longer hospitalization compared to dogs without lidocaine. Conclusion Lidocaine administration had no impact on the plasma levels of cytokines during the 48-h study period, but significantly lower CRP concentrations were found at T24 and T48. Lidocaine’s potential side effects require careful decision making regarding its use.